2011
DOI: 10.1155/2011/506501
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on Corrosion of Cast Iron Pipes

Abstract: It is well known that corrosion is the predominant mechanism for the deterioration of cast iron pipes, leading to the reduction of pipe capacity and ultimate collapse of the pipes. In order to assess the remaining service life of corroded cast iron pipes, it is imperative to understand the mechanisms of corrosion over a long term and to develop models for pipe deterioration. Although many studies have been carried out to determine the corrosion behavior of cast iron, little research has been undertaken to unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 24 publications
3
29
0
5
Order By: Relevance
“…No entanto, embora a fase ferrita apresente facilidade em formar filmes passivos, o fato de estar próxima a um material mais nobre, terá sua resistência diminuída. A fase eutética fosforosa foi a mais resistente à corrosão [13][14].…”
Section: Resultados E Discussõesunclassified
“…No entanto, embora a fase ferrita apresente facilidade em formar filmes passivos, o fato de estar próxima a um material mais nobre, terá sua resistência diminuída. A fase eutética fosforosa foi a mais resistente à corrosão [13][14].…”
Section: Resultados E Discussõesunclassified
“…Many studies have been conducted to detect the mechanisms and factors responsible for degradation. Mohebbi et al [25] found that localized corrosion (pitting) is the main form of corrosion in cast iron water pipes. Mehra et al [19] investigated the variation in corrosion rate and corrosion current density of gray cast iron as a function of immersion time in various salt solutions.…”
Section: *M O Azzougmentioning
confidence: 99%
“…Si bien es cierto que los productos de corrosión formados en la fundición gris no fueron analizados, es esperable que presente este mismo tipo de oxihidróxidos, tal como dice la literatura. [24,25], no siendo relevantes para este estudio, pues lo que se desea replicar es el comportamiento bimodal del material frente a la corrosión atmosférica marina.…”
Section: Análisis Morfológico De Productos De Corrosiónunclassified
“…El desarrollo de esta doble capa, poco antes de t a , indica la presencia de oxihidróxidos de hierro [29] que protegen al sustrato metálico del avance de la corrosión [30] que, al ralentizar la corrosión mediante una disminución en la difusión de oxígeno al sustrato, promueven las condiciones anaeróbicas para la corrosión bacteriana, producto de bacterias reductoras de sulfato (BRS). La acción de estas bacterias sería responsable del picado que aparece luego del punto de inflexión mencionado [31][32].…”
Section: Número De Ciclosunclassified